1997
DOI: 10.1111/1468-5884.00066
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evoked Potentials to Geometric Forms: Effects of Spatial Orientation

Abstract: Five outlined geometric figures of equal contour length were presented monocularly below the fixation point (FP); an upright equilateral triangle (upright triangle), an inverted equilateral triangle (inverted triangle), an upright square (square), a 45°‐tilted square (diamond) and a circle. The angular separation between FP and the top of the figures was held constant. Transient visual evoked potentials (VEPs) were recorded monopolarly from inion, 4, 7, 10 cm above it (l, l4, l7, l10) and Cz for ten subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…However, the orientation could be a crucial signal for shape discrimination (Ishii & Tsuji, 1979). Its effect must therefore be examined in order to identify the formspecific response (Ito et al, 1997). Experiment 2 therefore investigated the VEPs when the figures were inverted (see Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the orientation could be a crucial signal for shape discrimination (Ishii & Tsuji, 1979). Its effect must therefore be examined in order to identify the formspecific response (Ito et al, 1997). Experiment 2 therefore investigated the VEPs when the figures were inverted (see Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the importance of form to visual perception, we have conducted psychophysiological studies of its effect upon transient VEPs by using the fundamental geometric forms of the equilateral triangle, the square and the circle (Ito, Kuwabara, Sugata, Suzuki, & Kawai, 1996, 1998Ito & Sugata, 1995;Ito, Sugata, & Kuwabara, 1997). The main aims of these studies were to accumulate meaningful psychophysiological data on form perception by means of the VEP as an objective measure, to identify form-related VEP components, and to understand how information regarding form is processed in the underlying cortical areas.…”
mentioning
confidence: 99%
“…Both waves showed the monopolar potential distribution on the scalp, with the peaks at I5. The N wave is what we called N1 in our previous studies (Ito & Sugata, 1995;Ito et al, 1997). Figure 3 shows the averaged peak latencies of the N and P waves at four locations except Fz.…”
Section: Vep Recordingmentioning
confidence: 90%
“…The triangle elicited a significantly larger negative (N1) response than the square or the circle. Ito et al (1997) examined the effects of geometric form and orientation, and found that the upright triangle, the inverted triangle and the diamond evoked significantly larger N1 responses than the square and the circle.…”
mentioning
confidence: 99%
See 1 more Smart Citation